Case Study : Financial Management and Marital Quality of Long-Distance Marriage Families - Fiscarini, Santy; Putri, Jihan Apikasari; Riany, Yulina Eva (Journal of Family Sciences, 2024)
Long-distance marriages conducted by street vendors impact financial management, including financial recording, the ability to save, and the wife's role in economic management. In addition, interactions and communication are also affected by conflicts due to work demands and lack of communication. This study analyzes marriage quality and financial management among street vendors in families who undergo long-distance marriage. This study used a descriptive qualitative method with a purposive sampling technique. The participants in this study amounted to three husbands who worked as street vendors and had long-distance marriages, as well as five people from various walks of life. This research was conducted in Bogor City from April to May 2022. Data collection techniques were observation and semi-structured interviews with data analysis, including reduction, presentation, and conclusion drawing. The results showed that most street vendors experienced difficulties managing finances due to limited knowledge, but marriage quality has been maintained over the years. Long distance reduces the frequency of conflict, and the mutual acceptance of long-distance conditions before marriage makes married couples understand and respect each other. The conclusion of this study suggests the importance of external support and financial education for street vendors to improve marriage quality and financial management.